Routing strategies for energy harvesting wireless sensor networks - Nguyen, Nhat Cuong. (2013)
Many studies in Wireless Sensor Network (WSN) have been carried out to find and optimize newly proposed protocols. Depending on various types of applications, routing in WSN has faced a number of challenges, especailly regarding to enery concern. Therefore, many approaches to resolve existing problems have been considered. The purpose of this report is to provide a closer look to these approaches. Besides, this report also shows the detailed theory and simulation of Data centric approach with the typical and well-know protocol: Directed Diffusion.The protocol implemented in this report has several limitations such as MAC layer issue. Further research is needed to optimize and bring the simulation to be more practical in real life implementation.